Strategi Branding MRT Jakarta melalui Konten Media Sosial Instagram Dalam Membangun Citra Perusahaan - Maydar, Syalwa Fatikha; Azwar, Azwar (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Instagram is widely used by product and service companies, especially MRT Jakarta. In its development on social media, MRT Jakarta always has a strategy to build its branding better on social media every year. The purpose of this study is to determine the communication strategy conveyed by MRT Jakarta's Social Media Specialist through content in the form of promotions, announcements, and inspiration to reach the audience. The method used for the study is descriptive qualitative content analysis to understand the descriptive experience of informants as users and active followers of MRT Jakarta. Data was collected through interviews with three informants who have experience using MRT Jakarta's public transportation, as well as direct observation from social media regarding posts from year to year. This study uses stages in data analysis, namely data collection, data presentation, and drawing conclusions. The results of the study show that MRT Jakarta's strategy has significant developments every year and every year it always updates different content with its editing concept which is also informative and increasingly attracts attention. In addition, researchers found new insights into the dynamics of the marketing world, especially in managing social media to build the company's service image.